HAMA PENTING TANAMAN UBI JALAR (Ipomea batatas L.(Lamb)) DI KABUPATEN MINAHASA, MINAHASA UTARA, DAN KOTA TOMOHON - Pinontoan, Odi R.; Lengkong, Maxi; Makal, Henny V.G. (EUGENIA, 2011)
ABSTRACT The research aimed to identify important pests which attack sweet potato in the field. Field and laboratory research were conducted. The field research was carried out in sweet potato cropping areas in Minahasa Regency, North Minahasa regency andÂ  Tomohon. The laboratory research was conducted in plant pests and disease laboratory, Faculty of Agriculture Sam Ratulangi University Manado to idedntify the important pest species which were found on sweet potato plants. The duration of the study was four months starting from December 2010 until March 2011. Survey method was applied with purposive random sampling.Â  The research was used 4 period of plant growth namely 1 month, 2 months,3 months, and 4-5 months after planting. The result showed that there were five orders identified, attacking sweet potato since the age of 1-4 months in Minahasa regency, Tomohon and North Minahasa regency. The five orders were Orthoptera, Hemiptera, Homoptera, Lepidoptera, and Coleoptera. The damage on the leaves were caused by pests coreidae, Cicadelidae, Spodoptera sp (Noctuidae), Valanga sp (Acrididae), and Oxya sp. (Acrididae), whereas on the stem was Omphisa sp (Pyralidae). Damage on the tuber was caused by Gryllotalpa sp (Gryllotalpidae), Cylas formicarius (Curculionidae) and Oryctes sp (Dynastidae). Key words : Important Pest Plant Sweet Potatoes, Ipomea batatas L.